Pengaruh Harga Dan Cita Rasa Terhadap Keputusan Pembelian Mie Instan Indomie Dengan Citra Merek Sebagai Variabel Intervening (Studi Kasus Pada Mahasiwa Manajemen Angkatan 2019 FEB Universitas Muhammadiyah Metro) - Durotun Nasikah; Ratmono; Rina Eka Mayanti (Jurnal Manajemen DIVERSIFIKASI, 2024)
The purpose of this research was to find out whether price had an effect on brand image. Tofind out whether taste had an effect on brand image. To find out whether the price affects thepurchase decision. To find out whether taste had an effect on purchasing decisions. To findout whether the price and the taste affect purchasing decisions with brand image as theintervening variable. The sample of this research was 58 Management Batch Students of the2019 in Muhammadiyah University of Metro. Data were collected through questionnairesheets, and the data analysis used validity test, reliability test, normality test, homogeneitytest, linearity test of significance regression, and path analysis using the program (SPSS).The results showed that the price and the taste had a positive and significant effects onpurchasing decisions, the price and the taste had a positive and significant effects on brandimage, and the price and the taste had positive and significant effects on purchasingdecisions with brand image as the intervening variable.